A kind of port special tire tread rubber and its preparation process
By using modified aramid fiber and modified silicon carbide in port special tire tread glue, the thermal fatigue and crown damage problems of port tires when used in high temperature environments are solved, and the low heat generation, long life and high wear resistance of tread glue are achieved.
Patent Information
- Application Number
- CN202411036095.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-07-31
AI Technical Summary
When port tires are used under heavy loads and high temperature environments, they are prone to problems such as crown damage, thermal fatigue, cracks and tire blowouts, resulting in short service life and high cost.
A special port tire tread rubber is adopted, including smoke sheet rubber, neodymium-based butadiene rubber, modified aramid fiber, filler, softened oil, etc. The thermal conductivity and mechanical properties of the tread rubber are improved through the production method of modified aramid fiber and the addition of modified silicon carbide.
It reduces the compressed heat generation value of the tread glue, extends the service life, improves wear resistance and slippery resistance, and avoids the decline in mechanical properties caused by excessive addition of thermally conductive fillers.
Smart Images

Figure BDA0004971106080000121 
Figure BDA0004971106080000131
Abstract
Description
Technical Field
[0001] The present application relates to the field of tire rubber technology, and more specifically, to a special port tire tread rubber and a preparation process thereof. Background Art
[0002] In recent years, with the development of the economy, port construction has developed rapidly. Port tires are mainly used for port machinery such as reach stackers and forklifts in port terminal operations. The characteristics of port tires in use are: (1) Under heavy loads, the tire crown is damaged quickly and then discarded. For example, the service life of bridge crane tires is about 1 to 1.5 years, while the service life of reach stacker tires is only 3-6 months. (2) Under pressure, when "twisting", delamination, tearing, and tire blowout often occur, causing tire damage. As the demand for port machinery tires increases, it is estimated that the annual demand for yard bridge crane tires will be about 150,000; the annual demand for reach stacker tires will be about 450,000. As the demand continues to increase, users are paying more and more attention to service life and cost reduction issues.
[0003] The tread of a traditional tire is divided into three parts: tread rubber, base rubber and adhesive rubber. The three layers of rubber are distributed from the outside to the inside. The tread rubber is the outermost layer of the tire that contacts the road surface and has a pattern printed on the surface. It can give the tire traction, cushion the impact and swing during driving, and prevent the cord layer from being cut and punctured.
[0004] In the prior art, a Chinese invention patent application with application number CN2014100941166 discloses a highly wear-resistant engineering tire tread rubber, which is composed of the following components by weight: 100 parts of rubber, consisting of 60 to 80 parts of natural rubber and 40 to 20 parts of butadiene rubber; 45 to 55 parts of carbon black; 7 to 15 parts of white carbon black; 4 to 8 parts of operating oil; 1 to 4 parts of petroleum resin; 2 to 5 parts of zinc oxide; 2 to 3.5 parts of stearic acid; 1 to 3 parts of flow dispersant; 1.0 to 2.5 parts of protective wax; 1 to 3 parts of p-phenylenediamine antioxidant; 1 to 3 parts of ketoamine antioxidant; 1 to 3 parts of sulfur; 1 to 2 parts of accelerator; 0.8 to 3 parts of scorch retarder; 0.3 to 0.6 parts of scorch retarder.
[0005] The tread rubber is mainly made of natural rubber, with butadiene rubber replacing styrene-butadiene rubber, which improves the engineering tire's resistance to chipping and chipping and increases its wear resistance. However, when the port tire is in use, a large amount of heat will be generated due to friction and carrying heavy objects, and the thermal conductivity of natural rubber itself is low. The heat cannot be efficiently transferred to the outside world, causing a large amount of heat accumulation inside. The tire continues to run in a high temperature environment, which is prone to thermal fatigue and causes cracks or damage on the tire surface. Adding thermal conductive fillers to the rubber matrix can improve the thermal conductivity of the rubber material, but a high content of thermal conductive fillers will also cause the rubber material to generate high heat and deteriorate its mechanical properties. Summary of the invention
[0006] In order to reduce the compression heat value of the tread rubber and improve the aging resistance, the present application provides a port special tire tread rubber and a preparation process thereof.
[0007] In the first aspect, the present application provides a port special tire tread rubber, which adopts the following technical solution:
[0008] A tread rubber for a special port tire, comprising the following raw materials in parts by weight: 172.5-186 parts of a masterbatch, 1-1.8 parts of a vulcanizing agent, 0.5-1 parts of an accelerator, and 0.1-0.26 parts of a scorch retarder; the masterbatch comprises the following raw materials in parts by weight: 55-65 parts of a smoked sheet rubber, 35-45 parts of a neodymium-based butadiene rubber, 20-30 parts of a modified aramid fiber, 30-36 parts of a filler, 1.5-2.5 parts of a softening oil, 3-5 parts of zinc oxide, 1.8-2.2 parts of a lubricant, 1-2 parts of a high-temperature protective wax, 3-5 parts of an antioxidant, 1.5-2.5 parts of a dicyclopentadiene resin, and 1.8-2.2 parts of an anti-reversion agent;
[0009] The method for preparing the modified aramid fiber comprises: etching the aramid fiber with a phosphoric acid solution, performing a thermal oxidation treatment, and then impregnating the aramid fiber with a natural latex solution and drying the aramid fiber.
[0010] By adopting the above technical scheme, the smoked sheet rubber has good physical properties, good flexibility resistance and low heat generation. The neodymium-based butadiene rubber is a polybutadiene rubber with a high cis-1,4-structure content obtained by coordination polymerization with a rare earth catalyst. It has the advantages of high stereoregularity and adjustable relative molecular weight distribution. The molecular chain has high flexibility, can reduce tire hysteresis, reduce heat generation, and improve wear resistance and anti-skid performance. The two have good compatibility and can form a stable mixed system. They combine the advantages of natural rubber and synthetic rubber and have relatively excellent physical and mechanical properties.
[0011] Modified aramid fiber is used to replace part of the filler. Aramid fiber is a high-performance synthetic fiber with excellent properties such as high modulus, high strength, high temperature resistance, acid and alkali resistance and light weight. At the same time, aramid fiber also has excellent insulation and anti-aging properties. However, because it is a rigid molecule, the molecule has high symmetry, crystallinity and orientation, the surface is very smooth, and the bonding effect with the colloid is poor. Therefore, it is first etched with phosphoric acid to make grooves or cracks on the surface of the aramid fiber, roughen the fiber surface, increase the specific surface area of the aramid fiber, and then thermally oxidize it to completely decompose the oil layer on its surface, increase the oxygen-containing groups on the surface of the aramid fiber, and improve the interfacial bonding ability between the aramid fiber and the natural rubber solution; the natural latex solution is impregnated on the surface of the aramid fiber. The natural latex solution has good compatibility with the smoked sheet glue, which can improve the dispersion of the aramid fiber therein, thereby Increase the interface effect between aramid fiber and rubber matrix, thereby limiting the movement of rubber molecular chains, reducing the viscous deformation caused by the friction of rubber molecules, reducing the friction of rubber molecules, and thus reducing compression heat generation. In addition, natural latex forms a protective film on the aramid fiber. When the rubber is subjected to shear force, the protective layer on the surface of the aramid fiber is preferentially subjected to force to resist external force deformation. The deformation of the flexible interface formed between the aramid fiber and the natural rubber replaces part of the deformation of the smoked rubber and the filler. The heat generated by the deformation of the flexible interface layer is less than the heat generated by the deformation of the natural rubber and the filler. The heat generated by the natural latex protective layer is low, thereby reducing heat generation. Therefore, the compression heat generation of the tread rubber can be reduced, the aging rate can be reduced, the service life can be extended, and the mechanical strength such as tensile strength and tear strength of the tread rubber can be improved to avoid the mechanical properties of the rubber material from being reduced due to excessive addition of thermally conductive fillers.
[0012] Optionally, the preparation method of the modified aramid fiber is as follows:
[0013] (1) immersing the aramid fiber in a phosphoric acid solution with a concentration of 15-20 wt % at 40-50° C. for 2-3 hours, filtering, washing, drying, heating to 280-300° C., and keeping the temperature for 5-6 minutes to obtain a heat-treated fiber;
[0014] (2) repeatedly rinsing the heat-treated fiber with a dopamine solution and drying at 40-50° C. to obtain a pretreated fiber;
[0015] (3) Immersing the pretreated fiber in a natural latex solution, taking it out after 5-8 minutes, and drying it. The mass ratio of the pretreated fiber to the natural latex solution is 1:1.5-2.
[0016] By adopting the above technical scheme, the aramid fiber is first impregnated with a phosphoric acid solution to form a fuzzy peeling layer on the surface of the fiber, and significant grooves appear on the fiber surface to roughen the fiber surface. Then, thermal oxidation is used to remove the grease layer. Finally, a polydopamine layer is used to present an uneven surface on the aramid fiber surface, thereby improving the interfacial adhesion between the fiber and the natural latex solution.
[0017] Optionally, the natural latex solution comprises natural latex and modified silicon carbide in a mass ratio of 1:0.1-0.2.
[0018] By adopting the above technical scheme, the thermal conductivity of the rubber material increased significantly by silicon carbide particles, but the mechanical properties and low heat generation are not significantly improved. Because silicon carbide has an irregular morphology, surface inertness, and poor compatibility with the rubber matrix, it is difficult to achieve good dispersion in natural latex. Therefore, it is necessary to modify it to increase its dispersibility, reduce phonon scattering and phonon transmission distance, and reduce internal heat. The modified silicon carbide is attached to the aramid fiber with the natural latex solution to improve the thermal conductivity of the aramid fiber surface. The aramid fiber with modified silicon carbide loaded on the surface overlaps with each other in the tread rubber to form a heat conduction path, which increases the heat loss of the tread rubber and increases its anti-aging ability.
[0019] Optionally, the preparation method of the modified silicon carbide is:
[0020] Disperse silicon carbide in a sodium hydroxide solution with a concentration of 16-20wt%, react at 80-85°C for 10-12h, filter and dry, add to an ethanol solution of KH550 with a concentration of 5-7wt%, react at 75-80°C for 7-8h, filter and dry to obtain pretreated silicon carbide;
[0021] The graphene oxide is dispersed in deionized water, EDC, NHS and pretreated silicon carbide are added, and the mixture is stirred and reacted at 38-40° C. for 20-24 hours, filtered, washed and freeze-dried. The mass ratio of the graphene oxide to the pretreated silicon carbide is 1:6-8.
[0022] By adopting the above technical scheme, graphene oxide with good dispersibility is used as a dispersing carrier, EDC and NHS are used as activators of carboxyl groups on the surface of graphene oxide and catalysts for amidation reaction, silicon carbide particles and graphene oxide are connected by chemical bonds to form composite particles, and the covalent bonds of silicon carbide particles and graphene oxide are compounded to form a point-surface structure, so that the thermal conductivity of modified silicon carbide is increased, and it is helpful to improve the dispersibility of modified silicon carbide in natural latex, as well as the compatibility of modified silicon carbide and natural latex, and the strong interaction between silicon carbide and graphene oxide can slow down the phonons carrying heat between silicon carbide, silicon carbide and natural latex, and silicon carbide and smoked rubber. Phonon scattering at the interface reduces compression heat generation; graphene oxide is coated on the surface of silicon carbide particles, which not only promotes the dispersion of silicon carbide in natural latex and increases the mechanical strength of rubber materials, but also this coating structure can weaken the stress concentration problem caused by amorphous silicon carbide particles, thereby avoiding stress concentration and fracture of the tread rubber when it is under stress. Secondly, silicon carbide particles and graphene oxide are blended to enhance natural latex. Natural latex is attached to aramid fibers and is in a scattered state in the rubber. When the tread rubber is subjected to dynamic load, silicon carbide and graphene oxide are linked by strong interaction, which reduces the friction between silicon carbides, generates less heat, and reduces compression heat generation.
[0023] Optionally, calcium chloride is further added to the natural latex solution, and the mass ratio of natural latex to calcium chloride is 1:0.02-0.04.
[0024] By adopting the above technical scheme, since the natural latex solution contains silicon carbide modified with graphene oxide, the surface of graphene oxide contains more oxygen-containing functional groups, which can form negative charge electrostatic repulsion, so that the graphene oxide can be dispersed evenly and stably, and the natural latex also presents a negative potential balance, so the graphene oxide will not produce flocculation in the natural latex. Adding calcium chloride as a flocculant can make the latex particles lose the electrostatic repulsion, so that they collide with each other to produce flocculation. The graphene oxide-modified silicon carbide wrapped around the latex particles collide and bond with each other, so that the natural latex has enough time to form linear aggregates, and further close together to generate a gel with a network structure, and then form a rubber block with a uniform structure, so as to obtain a natural latex product with a relatively complete molecular chain and a high relative molecular weight, reduce the internal friction of the rubber, and obtain low heat generation performance.
[0025] Optionally, calcium chloride is further added to the natural latex solution, and the mass ratio of natural latex to calcium chloride is 1:0.02-0.04.
[0026] By adopting the above technical solution, modified nanocellulose replaces part of the carbon black, reducing the density of the carbon black network. The modified nanocellulose can also act as a lubricating particle, hindering the formation of the carbon black network and reducing the energy consumption in the process of breaking and reorganizing the filler network, thereby improving the dispersion of the filler and reducing the rolling resistance. Nanocellulose can also increase the active volume of the molecular chain, improve processing fluidity, enhance the vulcanization promotion effect of the rubber, and at the same time increase the crosslinking density, shorten the vulcanization time, increase the tensile strength and tear strength, and improve the wear resistance.
[0027] Optionally, the preparation method of the modified nanocellulose is as follows:
[0028] Disperse nanocellulose in deionized water, add zinc acetate dihydrate, heat to 80-90°C, stir for 1-1.5h, adjust pH to 10-11 with sodium hydroxide solution, stir for 30-40min, filter, dry, and obtain an intermediate, wherein the mass ratio of nanocellulose to zinc acetate dihydrate is 1:0.15-0.25;
[0029] The intermediate is dispersed in deionized water, hexadecyltrimethylammonium bromide is added, the temperature is raised to 60-70° C., the reaction is carried out for 2-3 hours, and the modified nanocellulose is obtained by centrifugation. The mass ratio of hexadecyltrimethylammonium bromide to the intermediate is 1:1.
[0030] By adopting the above technical scheme, zinc acetate is used as a precursor, and zinc oxide is loaded on the surface of nanocellulose by a sol-gel method, thereby promoting the vulcanization effect, improving the wear resistance and resistance to permanent compression deformation of the tread rubber, improving the dispersion performance of the filler, and reducing the rolling resistance; and then cetyltrimethylammonium bromide is used on the intermediate to perform physical adsorption through electrostatic interaction, which is beneficial to improve the dispersion state of nanocellulose in the rubber, prevent its agglomeration, improve the interface bonding between nanocellulose and rubber, increase the tensile strength and tear strength, and to a certain extent, well prevent the formation and expansion of cracks, improve wear resistance, and reduce its calorific value.
[0031] Optionally, the carbon black is pretreated as follows:
[0032] Disperse carbon black in deionized water to form a dispersion with a concentration of 3-5wt%, add sodium thiosulfate, stir evenly to form a suspension, add a 30wt% hydrochloric acid solution, stir, wash with deionized water to a pH of 7, freeze-dry, and the mass ratio of carbon black to sodium thiosulfate and hydrochloric acid solution is 3.3:6-8:50-60.
[0033] By adopting the above technical scheme, nano-sulfur modified carbon black is used as a part of the filler, sulfur is formed on the carbon black by chemically depositing sulfur, the sulfur can directly act on the surface of the carbon black, and then added to a masterbatch, when the masterbatch is mixed, the high temperature causes the sulfur to be melted, and can be more evenly blended with the smoke sheet rubber, effectively ensuring that the sulfur and carbon black are evenly dispersed in the tread rubber, and the sulfur deposited on the surface of the carbon black can react with the double bonds of the rubber molecular chain at high temperature, so that a connection is formed between the carbon black and the rubber, promoting a strong interaction between the carbon black and the rubber, and increasing the tensile strength and the tear strength, the nano-sulfur with a smaller particle size deposited on the surface can make the rubber material have a more uniform cross-linked network structure, further restrict the movement of the rubber molecular chain wrapped on the surface of the carbon black, reduce the friction between the carbon black and the rubber molecular chain, improve the vulcanization performance, and reduce the interface thermal resistance.
[0034] Optionally, the antioxidant includes antioxidant RD and antioxidant 4020 in a mass ratio of 1.5:2.5-3.5;
[0035] The softening oil is selected from at least one of aromatic oil, naphthenic oil and paraffin oil;
[0036] The lubricant is selected from at least one of stearic acid, paraffin oil and silicone oil;
[0037] The scorch retarder is selected from at least one of N-cyclohexylthiophthalimide and N,N-dibenzhydryl-1,6-hexanediisocyanate;
[0038] The accelerator is selected from at least one of accelerator DM, accelerator NS and accelerator TMTD;
[0039] The vulcanizing agent is selected from at least one of sulfur, benzoyl peroxide or sulfur monochloride;
[0040] The anti-reversion agent is anti-reversion agent WK-901 or PK-900.
[0041] By adopting the above technical solution, the antioxidant reduces the influence of external factors such as heat, mechanical stress, light and chemical corrosion on the tread rubber, prevents it from degradation and aging, and thus causes the tread rubber to lose its use value.
[0042] Lubricants can form a lubricating film on the rubber surface, reduce the friction resistance in rubber mixing, extrusion, calendering and other processes, and improve processing performance and product quality.
[0043] Softening oil can play the role of plasticization, softening and filling, and can improve the processing performance and physical properties of rubber. Aromatic oil is mainly composed of aromatic hydrocarbons, with good compatibility and comprehensive performance. Cycloalkane oil is mainly composed of cycloalkanes, with good low-temperature performance, and can reduce the brittle temperature of rubber. Paraffin oil is mainly composed of straight-chain alkanes, which can improve the rubber's antioxidant properties and high temperature resistance.
[0044] Anti-scorch agents are mainly used to prevent premature vulcanization of rubber during processing, extend the mixing and processing time of rubber, and avoid hardening or coking of rubber when the expected degree of vulcanization has not been reached.
[0045] Accelerators can accelerate the vulcanization process, reduce the vulcanization temperature, shorten the vulcanization time, and improve the physical and mechanical properties and aging resistance of rubber.
[0046] Vulcanizing agents are used to cross-link rubber molecules, making the tread rubber have better elasticity, wear resistance, oil resistance and other properties, thereby increasing the service life of the rubber.
[0047] Anti-reversion agent is mainly used to prevent rubber from reversion to its original state under long-term high temperature, thereby extending the service life of tread rubber.
[0048] In the second aspect, the present application provides a process for preparing a tread rubber for a special port tire, which adopts the following technical solution:
[0049] A preparation process of a tread rubber for a special port tire comprises the following steps:
[0050] Mixing cigarette sheet rubber, neodymium-based butadiene rubber, modified aramid fiber, filler, softening oil, zinc oxide, lubricant, high temperature protective wax, antioxidant, dicyclopentadiene resin and anti-vulcanization reversion agent, and debonding at 155-165° C. to obtain a masterbatch;
[0051] The master rubber is mixed with a vulcanizing agent, an accelerator and a scorch retarder, and kneaded, and discharged at 95-105° C. to obtain a tread rubber.
[0052] By adopting the above technical solution and using modified aramid fiber to replace a part of the filler, the compression heat generation of the tread rubber can be improved and its mechanical strength can be increased.
[0053] In summary, this application has the following beneficial effects:
[0054] 1. Since the present application adopts smoked rubber and neodymium-based butadiene rubber as the main materials, and uses modified aramid fiber to replace part of the filler, the aramid fiber is impregnated with a phosphoric acid solution and then heat-treated and impregnated with a natural latex solution, which can improve the dispersion of the aramid fiber in a masterbatch, limit the movement of the rubber molecular chain, reduce compression heat generation, resist external force deformation, and improve mechanical strength and wear resistance.
[0055] 2. In the present application, it is preferred to add modified silicon carbide to the natural latex solution, wherein the modified silicon carbide uses graphene oxide as a dispersion carrier. The modified silicon carbide is attached to the aramid fiber by the adhesive force of the natural latex, forming a heat conduction channel in the tread rubber, reducing internal heat generation, improving the dispersibility of the modified silicon carbide, improving the interfacial bonding ability between the aramid fiber and the rubber material, further restricting the movement of the rubber molecular chain, reducing the heating value, improving the thermal aging of the tread rubber, and increasing the service life.
[0056] 3. In this application, modified nanocellulose is used to replace part of the carbon black, which can improve the dispersibility of carbon black, increase the crosslinking density, improve the mechanical properties of the tread rubber such as tensile strength, and improve wear resistance. In addition, nano-sulfur is used to modify the carbon black to increase the connection between the carbon black and rubber molecules, reduce the friction of the molecular chains, and reduce compression heat generation. DETAILED DESCRIPTION
[0057] The following examples further illustrate the present application in detail.
[0058] Preparation Example 1-9 of Modified Aramid Fiber
[0059] Preparation Example 1: (1) 100 g of aramid fiber was immersed in 2000 g of 20 wt% phosphoric acid solution at 40°C for 3 h, filtered, washed with distilled water, dried at 60°C, heated to 300°C, and kept warm for 5 min to obtain heat-treated fiber. The aramid fiber was selected from Taekwang, Korea, type I 1414, YD1500, 2D×51 mm;
[0060] (2) The heat-treated fiber is immersed in a natural latex solution, taken out after 8 minutes, and dried at 80° C. The mass ratio of the heat-treated fiber to the natural latex solution is 1:2. The natural latex solution is selected from Jinan Century Tiancheng Chemical Co., Ltd., model number rj007.
[0061] Preparation Example 2: (1) 100 g of aramid fiber was immersed in 2000 g of 15 wt% phosphoric acid solution at 50°C for 2 h, filtered, washed with distilled water, dried at 60°C, heated to 280°C, and kept warm for 6 min to obtain heat-treated fiber. The aramid fiber was selected from Taekwang, Korea, type I 1414, YD1500, 2D×51 mm;
[0062] (2) The heat-treated fiber is immersed in a natural latex solution, taken out after 5 minutes, and dried at 80° C. The mass ratio of the heat-treated fiber to the natural latex solution is 1:1.5. The natural latex solution is selected from Jinan Century Tiancheng Chemical Co., Ltd., model number rj007.
[0063] Preparation Example 3: The difference from Preparation Example 1 is that only a phosphoric acid solution with a concentration of 20 wt % is used for immersion treatment at 50° C. for 2 h.
[0064] Preparation Example 4: The difference from Preparation Example 1 is that the heat treatment is only performed at 300°C for 5 minutes.
[0065] Preparation Example 5: The difference from Preparation Example 1 is that only the natural latex solution is used for immersion for 8 minutes, and the mass ratio of the natural latex solution to the aramid fiber is 2:1.
[0066] Preparation Example 6: (1) 100 g of aramid fiber was immersed in 2000 g of 20 wt% phosphoric acid solution at 40°C for 3 h, filtered, washed with distilled water, dried at 60°C, heated to 300°C, and kept warm for 5 min to obtain heat-treated fiber. The aramid fiber was selected from Taekwang, Korea, type I 1414, YD1500, 2D×51 mm;
[0067] (2) preparing a Tris-HCl buffer solution (pH=8.5), adding dopamine hydrochloride to prepare a dopamine solution with a concentration of 2 g / L, repeatedly rinsing the heat-treated fiber with the dopamine solution for 3 times, and vacuum drying at 40° C. to obtain a pretreated fiber;
[0068] (3) The pretreated fiber was immersed in a natural latex solution, taken out after 8 minutes, and dried at 80°C. The mass ratio of the pretreated fiber to the natural latex solution was 1:2. The natural latex solution was selected from Jinan Century Tiancheng Chemical Co., Ltd., model number rj007.
[0069] Preparation Example 7: The difference from Preparation Example 6 is that the natural latex solution includes natural latex and modified silicon carbide in a mass ratio of 1:0.1, the natural latex is selected from Jinan Century Tiancheng Chemical Co., Ltd., model rj007, and the modified silicon carbide is prepared by the following method: dispersing silicon carbide in a sodium hydroxide solution with a concentration of 16wt%, reacting at 80°C for 10h, filtering, drying, adding to an ethanol solution of KH550 with a concentration of 7wt% (prepared by mixing ethanol and water in a mass ratio of 7:1), reacting at 80°C for 7h, filtering, washing with ethanol and deionized water for 5 times respectively, and vacuum drying at 60°C for 12h to obtain pretreated silicon carbide;
[0070] 50 g of graphene oxide was dispersed in 1 L of deionized water, and 0.2 g of EDC, 0.2 g of NHS and pretreated silicon carbide were added. The mixture was stirred and reacted at 40 °C for 20 h, filtered, washed and freeze-dried for 24 h (-40 °C, 40 Pa). The mass ratio of graphene oxide to pretreated silicon carbide was 1:6.
[0071] Preparation Example 8: The difference from Preparation Example 6 is that the natural latex solution includes natural latex and modified silicon carbide in a mass ratio of 1:0.2, the natural latex is selected from Jinan Century Tiancheng Chemical Co., Ltd., model rj007, and the modified silicon carbide is prepared by the following method: dispersing silicon carbide in a sodium hydroxide solution with a concentration of 20wt%, reacting at 85°C for 12h, filtering, drying, adding to an ethanol solution of KH550 with a concentration of 5wt% (prepared by mixing ethanol and water in a mass ratio of 7:1), reacting at 75°C for 8h, filtering, washing with ethanol and deionized water for 3 times respectively, and vacuum drying at 60°C for 12h to obtain pretreated silicon carbide;
[0072] 50 g of graphene oxide was dispersed in 1 L of deionized water, and 0.2 g of EDC and 0.2 g of NHS and pretreated silicon carbide were added. The mixture was stirred and reacted at 38 ° C for 24 h, filtered, washed, and freeze-dried for 24 h (-40 ° C, 40 Pa). The mass ratio of graphene oxide to pretreated silicon carbide was 1:8.
[0073] Preparation Example 9: The difference from Preparation Example 8 is that calcium chloride is also added to the natural latex solution, and the mass ratio of calcium chloride to natural latex is 1:0.04.
[0074] Example
[0075] Example 1: A tread rubber for a special port tire, comprising 172.5 kg of a masterbatch, 1.4 kg of a vulcanizing agent, 0.7 kg of an accelerator and 0.18 kg of an anti-scorching agent, wherein the vulcanizing agent is sulfur, the accelerator is an accelerator NS, and the anti-scorching agent is CTP. The amount of the masterbatch is shown in Table 1. In Table 1, the smoked sheet rubber is 3# smoked sheet rubber, selected from Jiangsu Bohai Rubber and Plastic Technology Co., Ltd., with the item number RSS3, the neodymium-based butadiene rubber is selected from Shanghai Duokang Industry, with the item number CB24, and the modified aramid fiber is prepared by Preparation Example 1. The filler is carbon black, model N234, the softening oil is aromatic oil, selected from Shandong Xinjiu New Material Technology Co., Ltd., with the item number TC-FTY, the lubricant is stearic acid, the high temperature protective wax is selected from Henan Jiapei Environmental Protection Technology Co., Ltd., with the item number LY-03, the antioxidants include antioxidant RD and antioxidant 4020 with a mass ratio of 1.5:2.5, the dicyclopentadiene resin is selected from Guangzhou Qian'an Chemical Co., Ltd., with the model XD-1000, and the anti-aging reversion agent is selected from Germany Lanxess, with the model PK-900.
[0076] The preparation process of the above-mentioned port special tire tread rubber comprises the following steps:
[0077] S1, mixing tobacco sheet rubber, neodymium-based butadiene rubber, modified aramid fiber, carbon black, softening oil, zinc oxide, lubricant, high temperature protective wax, antioxidant, dicyclopentadiene resin and anti-vulcanization reversion agent, and debonding at 165° C. to obtain a masterbatch;
[0078] S2, mixing the masterbatch with a vulcanizing agent, an accelerator and a scorch retarder, and kneading the mixture, and discharging the mixture at 105° C. to obtain a tread rubber.
[0079] Table 1 Amount of raw materials used for tread rubber in Examples 1-3
[0080] Raw material / kg Example 1 Example 2 Example 3 Smoked glue 60 55 65 Neodymium butadiene rubber 40 45 35 Modified aramid fiber 20 30 30 filler 36 30 36 Softening oil 2 2.5 1.5 Zinc Oxide 4 3 5 Lubricants 2 1.8 2.2 High temperature protective wax 1.5 1 2 Antioxidant 4 3 5 Dicyclopentadiene resin 2 1.5 2.5 Anti-reversion agent 1 2.2 1.8
[0081] Example 2: A tread rubber for a special tire for a port, comprising 175 kg of a masterbatch, 1.0 kg of a vulcanizing agent, 0.5 kg of an accelerator and 0.1 kg of an anti-scorching agent, wherein the vulcanizing agent is sulfur, the accelerator is an accelerator NS, and the anti-scorching agent is CTP. The amount of the masterbatch is shown in Table 1. In Table 1, the smoke sheet rubber is 3# smoke sheet rubber, selected from Jiangsu Bohai Rubber and Plastic Technology Co., Ltd., with the item number RSS3, the neodymium-based butadiene rubber is selected from Shanghai Duokang Industry, with the item number CB24, and the modified aramid fiber is prepared from Preparation Example 2. The filler is carbon black, model N234, the softening oil is aromatic oil, selected from Shandong Xinjiu New Material Technology Co., Ltd., item number TC-FTY, the lubricant is stearic acid, the high temperature protective wax is selected from Henan Jiapei Environmental Protection Technology Co., Ltd., item number LY-03, the antioxidant includes antioxidant RD and antioxidant 4020 with a mass ratio of 1.5:3, the dicyclopentadiene resin is selected from Guangzhou Qian'an Chemical Co., Ltd., model XD-1000, and the anti-aging reversion agent is selected from Germany Lanxess, model PK-900.
[0082] The preparation process of the above-mentioned port special tire tread rubber comprises the following steps:
[0083] S1, mixing tobacco sheet rubber, neodymium-based butadiene rubber, modified aramid fiber, carbon black, softening oil, zinc oxide, lubricant, high temperature protective wax, antioxidant, dicyclopentadiene resin and anti-vulcanization reversion agent, and debonding at 155° C. to obtain a masterbatch;
[0084] S2, mixing the masterbatch with the vulcanizing agent, the accelerator and the scorch retarder, and performing internal kneading, and performing rubber discharge at 95° C. to obtain the tread rubber.
[0085] Example 3: A tread rubber for a special port tire, comprising 186 kg of a masterbatch, 1.8 kg of a vulcanizing agent, 1 kg of an accelerator and 0.26 kg of a scorch retarder, wherein the vulcanizing agent is sulfur, the accelerator is an accelerator NS, the scorch retarder is CTP, and the amount of the masterbatch is as shown in Table 1. In Table 1, the smoked sheet rubber is 3# smoked sheet rubber, selected from Jiangsu Bohai Rubber & Plastic Technology Co., Ltd., with the article number RSS3, the neodymium-based butadiene rubber is selected from Shanghai Duokang Industry, with the article number CB24, and the modified aramid fiber is prepared by Preparation Example 1. The filler is carbon black, model N234, the softening oil is aromatic oil, selected from Shandong Xinjiu New Material Technology Co., Ltd., item number TC-FTY, the lubricant is stearic acid, the high temperature protective wax is selected from Henan Jiapei Environmental Protection Technology Co., Ltd., item number LY-03, the antioxidant includes antioxidant RD and antioxidant 4020 with a mass ratio of 1.5:3.5, the dicyclopentadiene resin is selected from Guangzhou Qian'an Chemical Co., Ltd., model XD-1000, and the anti-aging reversion agent is selected from Germany Lanxess, model PK-900.
[0086] The preparation process of the above-mentioned port special tire tread rubber comprises the following steps:
[0087] S1, mixing tobacco sheet rubber, neodymium-based butadiene rubber, modified aramid fiber, carbon black, softening oil, zinc oxide, lubricant, high temperature protective wax, antioxidant, dicyclopentadiene resin and anti-vulcanization reversion agent, and debonding at 160° C. to obtain a masterbatch;
[0088] S2, mixing the masterbatch with a vulcanizing agent, an accelerator and a scorch retarder, and performing internal kneading, and discharging the masterbatch at 100° C. to obtain a tread rubber.
[0089] Example 4: A special tire tread rubber for ports, which differs from Example 1 in that the modified aramid fiber is made from Preparation Example 6.
[0090] Example 5: A special tire tread rubber for ports, which differs from Example 1 in that the modified aramid fiber is made from Preparation Example 7.
[0091] Example 6: A special tire tread rubber for ports, which is different from Example 1 in that the modified aramid fiber is made from Preparation Example 8.
[0092] Example 7: A special tire tread rubber for ports, which is different from Example 6 in that the modified aramid fiber is made from Preparation Example 9.
[0093] Embodiment 8: A tread rubber for special port tires, which is different from Embodiment 7 in that the filler comprises carbon black and modified nanocellulose in a mass ratio of 1:0.5, and the modified nanocellulose is prepared by the following method:
[0094] Disperse 20 g of nanocellulose in 100 mL of deionized water, add zinc acetate dihydrate, heat to 80°C, stir for 1.5 h, adjust the pH to 11 with a 20 wt% sodium hydroxide solution, stir and react for 40 min, filter, and vacuum dry at 80°C for 6 h to obtain an intermediate, where the mass ratio of nanocellulose to zinc acetate dihydrate is 1:0.25;
[0095] The intermediate was dispersed in 200 g of deionized water, hexadecyltrimethylammonium bromide was added, the temperature was raised to 60° C., the reaction was carried out for 3 h, and the mixture was centrifuged at a speed of 4000 r / min to obtain modified nanocellulose, wherein the mass ratio of hexadecyltrimethylammonium bromide to the intermediate was 1:1.
[0096] Example 9: A tread rubber for a special port tire, which is different from Example 7 in that the filler comprises carbon black and modified nanocellulose in a mass ratio of 1:0.3, and the modified nanocellulose is prepared by the following method:
[0097] Disperse 20 g of nanocellulose in 100 mL of deionized water, add zinc acetate dihydrate, heat to 90°C, stir for 1 hour, adjust the pH to 10 with a 20 wt% sodium hydroxide solution, stir for 30 minutes, filter, and vacuum dry at 80°C for 6 hours to obtain an intermediate, where the mass ratio of nanocellulose to zinc acetate dihydrate is 1:0.15;
[0098] The intermediate was dispersed in 200 g of deionized water, hexadecyltrimethylammonium bromide was added, the temperature was raised to 70° C., the reaction was carried out for 2 h, and the modified nanocellulose was obtained by centrifugation at a speed of 4000 r / min. The mass ratio of hexadecyltrimethylammonium bromide to the intermediate was 1:1.
[0099] Embodiment 10: A tread rubber for special port tires, which is different from Embodiment 8 in that the filler comprises carbon black and modified nanocellulose in a mass ratio of 1:0.5, and the modified nanocellulose is prepared by the following method:
[0100] Disperse 20 g of nanocellulose in 100 mL of deionized water, add zinc acetate dihydrate, heat to 80°C, stir for 1.5 h, adjust the pH to 11 with 20 wt% sodium hydroxide solution, stir and react for 40 min, filter, and vacuum dry at 80°C for 6 h to modify the nanocellulose. The mass ratio of nanocellulose to zinc acetate dihydrate is 1:0.25.
[0101] Example 11: A tread rubber for a special tire for ports. The difference from Example 8 is that the filler includes carbon black and modified nanocellulose in a mass ratio of 1:0.5, and the modified nanocellulose is made by the following method: add 20g of nanocellulose to 200g of deionized water, add hexadecyltrimethylammonium bromide, heat to 60°C, react for 3h, and centrifuge at 4000r / min to obtain modified nanocellulose. The mass ratio of hexadecyltrimethylammonium bromide to the intermediate is 1:1.
[0102] Example 12: A tread rubber for special port tires, which is different from Example 8 in that the carbon black in the filler is pretreated as follows:
[0103] Disperse 3.3 g of carbon black in deionized water to form a dispersion with a concentration of 5 wt%, add sodium thiosulfate, stir evenly to form a suspension, add 50 g of 30 wt% hydrochloric acid solution to a pH of 7, filter, and freeze-dry. The mass ratio of carbon black to sodium thiosulfate is 3.3:6:50.
[0104] Example 13: A special port tire tread rubber, which is different from Example 8 in that the carbon black in the filler is pretreated as follows:
[0105] Disperse 3.3 g of carbon black in deionized water to form a dispersion with a concentration of 3 wt%, add sodium thiosulfate, stir evenly to form a suspension, add 60 g of 30 wt % hydrochloric acid solution to pH 7, filter, and freeze-dry. The mass ratio of carbon black to sodium thiosulfate is 3.3:8:60.
[0106] Comparative Example
[0107] Comparative Example 1: A tread rubber for a special port tire, which differs from Example 1 in that an equal amount of aramid fiber is used to replace the modified aramid fiber.
[0108] Comparative Example 2: A tread rubber for a special port tire, which is different from Example 1 in that the modified aramid fiber is made from Preparation Example 3.
[0109] Comparative Example 3: A special tire tread rubber for ports, which is different from Example 1 in that the modified aramid fiber is made from Preparation Example 4.
[0110] Comparative Example 4: A special port tire tread rubber, which is different from Example 1 in that the modified aramid fiber is made from Preparation Example 5.
[0111] Comparative Example 5: A tread rubber for a special port tire, which differs from Example 1 in that an equal amount of carbon black is used to replace the modified aramid fiber.
[0112] Comparative Example 6: A tread rubber for a special port tire, which differs from Example 1 in that an equal amount of silicon carbide is used to replace the modified aramid fiber.
[0113] Comparative Example 7: A high wear-resistant engineering tire tread rubber, including 60kg 3# smoked sheet rubber, 40kg butadiene rubber 9000, 55kg carbon black 220, 8kg precipitated silica with a particle size of 11-110nm, 6kg aromatic oil, 2kg coumarone petroleum resin, 3.5kg zinc oxide, 3.5kg stearic acid, 2kg flow dispersant FC-608, 2.5kg rubber protective wax RPW-1, 2kg antioxidant 4010NA, 1.5kg antioxidant RD, 1.4kg sulfur, 0.8kg accelerator NS, 0.4kg anti-scorch agent CTP. Rubber refining is carried out according to the specified components, and the mixing of the rubber material is carried out in three stages. The first and second stage mixing was carried out in a BB370 type internal mixer (in the first stage mixing, the mixing temperature was 165-172°C, the rotation speed was 45-60r / min, and the mixing time was 2.5-3.5min; in the second stage mixing, the mixing temperature was 145-152°C, the rotation speed was 40-50r / min, and the mixing time was 2.0-3.0min), and the third stage mixing was carried out in a GK-270 type internal mixer (mixing temperature was 95-110°C, the rotation speed was 20-30r / min, and the mixing time was 4-5min). The feeding order was the conventional feeding order.
[0114] Performance testing
[0115] The tread rubber was prepared according to the methods in the examples and comparative examples, and the performance was tested according to the following methods. The test results are recorded in Table 2.
[0116] 1. Tensile strength: The test is carried out in accordance with GB / T528-1998 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" at room temperature and a tensile speed of 500 mm / min.
[0117] 2. Tear strength: Test in accordance with GB / T529-1999 "Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled)".
[0118] 3. Compression heating: According to GB / T1687-93 "Compression flexure test for determination of temperature rise and fatigue resistance of vulcanized rubber in flexure test", the compression heating test of the vulcanized rubber is carried out using RH-3000N compression fatigue heating testing machine. The sample is a cylinder of φ17.8mm×25mm. The test conditions are 55℃, frequency is 30Hz, prestress is 1MPa, strain amplitude is 4.45mm, and test time is 25min.
[0119] 4. DIN wear volume: Tested in accordance with GB / T9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber".
[0120] 5. Thermal conductivity: Tested in accordance with GB / T11205-2009 "Hot wire method for determination of thermal conductivity of rubber".
[0121] Table 2 Performance test results of tread rubber
[0122]
[0123]
[0124] It can be seen from the data in Table 2 that the modified aramid fibers prepared in Preparation Examples 1 and 2 in Examples 1-3 are used to replace part of the carbon black, which can effectively improve the tensile strength and tear strength of the tread rubber, reduce the compression heat value, and improve the wear resistance of the tread rubber. In Comparative Example 1, unmodified aramid fibers are used, which have low interfacial bonding with rubber molecules due to their inert surface, resulting in decreased mechanical properties of the tread rubber, increased heat value, and reduced wear resistance.
[0125] Comparative Example 2 uses the modified aramid fiber prepared in Preparation Example 3. Compared with Preparation Example 1, the aramid fiber is treated with phosphoric acid solution only. The compression heat value of the tread rubber prepared by the modified aramid fiber increases, and the tensile strength and tear strength decrease. However, compared with the unmodified aramid fiber used in Comparative Example 1, the heat value of the tread rubber in Comparative Example 2 decreases, indicating that the phosphoric acid solution treatment can increase the interfacial bonding strength between the aramid fiber and the rubber. Comparative Example 3 uses the modified aramid fiber prepared in Preparation Example 4. The aramid fiber is only heat-treated. Compared with Example 1, the compression heat value increases and the mechanical properties decrease. Comparative Example 4 uses the modified aramid fiber prepared in Preparation Example 5. It is only impregnated with natural latex solution. Although the interfacial bonding effect can be improved, the crosslinking density decreases and the heat value increases.
[0126] In Comparative Example 5, an equal amount of carbon black is used to replace the modified aramid fiber. Compared with Example 1, the tensile strength and tear resistance of the tread rubber decrease, the calorific value increases, and the wear resistance decreases.
[0127] In Comparative Example 6, an equal amount of silicon carbide is used to replace the modified aramid fiber. Although the thermal conductivity coefficient increases, the compression heat generation value increases, and the tensile and tear resistance strengths are lower than those in Example 1.
[0128] Comparative Example 7 is an engineering tire tread rubber provided in the prior art, which has a high tear strength but a high compression heat generation value.
[0129] Example 4 uses the modified aramid fiber prepared in Preparation Example 6. Compared with Preparation Example 1, dopamine solution is also used to elute the heat-treated fiber to form a polydopamine layer on the aramid fiber, thereby improving its interface with natural latex and increasing the tensile strength and tear strength of the tread rubber.
[0130] In Example 5 and Example 6, modified aramid fibers prepared in Preparation Example 7 and Preparation Example 8 are used respectively. Compared with Preparation Example 6, modified silicon carbide is also added to the natural latex solutions used in Preparation Example 7 and Preparation Example 8. Compared with Example 4, the thermal conductivity of the tread rubber prepared in Example 5 and Example 6 is increased, and the compression heat generation is reduced, the tensile strength and tear strength are improved, and the wear resistance is enhanced.
[0131] In Example 7, the modified aramid fiber prepared in Preparation Example 9 was used, wherein calcium chloride was further added to the natural rubber latex solution. Compared with Example 6, the tread rubber prepared in Example 7 had a further reduced compression heat value as shown in Table 2.
[0132] Compared with Example 7, Examples 8 and 9 use carbon black and modified nanocellulose as fillers. Table 2 shows that although the thermal conductivity does not change much, the tensile strength and tear strength of the tread rubber increase, the mechanical properties are improved, the compression heat value decreases, and the heat aging resistance is enhanced.
[0133] In Example 10, carbon black and modified nanocellulose are used as fillers, and sodium lauryl sulfate is not added when preparing the modified nanocellulose. Compared with Example 8, the tensile strength and tear strength of the tread rubber decrease, and the compression heat generation value increases.
[0134] In Example 11, compared with Example 8, zinc acetate dihydrate was not used in the preparation of modified nanocellulose, so the mechanical strength of the tread rubber prepared thereby decreased and the calorific value increased.
[0135] Compared with Example 8, Example 12 also uses sulfur to be deposited on the surface of carbon black, so that the tread rubber prepared thereby has increased tensile strength and tear strength, reduced calorific value, and improved wear resistance.
[0136] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A tread rubber for special port tires, characterized in that: The invention comprises the following raw materials in parts by weight: 172.5-186 parts of a masterbatch, 1-1.8 parts of a vulcanizing agent, 0.5-1 parts of an accelerator, and 0.1-0.26 parts of a scorch retarder; the masterbatch comprises the following raw materials in parts by weight: 55-65 parts of smoked sheet rubber, 35-45 parts of neodymium-based butadiene rubber, 20-30 parts of modified aramid fiber, 30-36 parts of filler, 1.5-2.5 parts of softening oil, 3-5 parts of zinc oxide, 1.8-2.2 parts of a lubricant, 1-2 parts of a high-temperature protective wax, 3-5 parts of an antioxidant, 1.5-2.5 parts of a dicyclopentadiene resin, and 1.8-2.2 parts of an anti-vulcanization reversion agent; The preparation method of the modified aramid fiber is as follows: (1) Immersing the aramid fiber in a phosphoric acid solution with a concentration of 15-20wt% at 40-50°C for 2-3h, filtering, washing, drying, heating to 280-300°C, and keeping the temperature for 5-6min to obtain a heat-treated fiber; (2) repeatedly rinsing the heat-treated fiber with a dopamine solution and drying at 40-50° C. to obtain a pretreated fiber; (3) immersing the pretreated fiber in a natural latex solution, taking it out after 5-8 minutes, and drying it, wherein the mass ratio of the pretreated fiber to the natural latex solution is 1:1.5-2; The natural latex solution comprises natural latex and modified silicon carbide in a mass ratio of 1:0.1-0.2; The preparation method of the modified silicon carbide: Disperse silicon carbide in a sodium hydroxide solution with a concentration of 16-20wt%, react at 80-85°C for 10-12h, filter and dry, add to an ethanol solution of KH550 with a concentration of 5-7wt%, react at 75-80°C for 7-8h, filter and dry to obtain pretreated silicon carbide; The graphene oxide is dispersed in deionized water, EDC, NHS and pretreated silicon carbide are added, and the mixture is stirred and reacted at 38-40° C. for 20-24 hours, filtered, washed and freeze-dried. The mass ratio of the graphene oxide to the pretreated silicon carbide is 1:6-8.
2. The port special tire tread rubber according to claim 1, characterized in that: Calcium chloride is also added to the natural latex solution, and the mass ratio of natural latex to calcium chloride is 1:0.02-0.
04.
3. The port special tire tread rubber according to claim 1, characterized in that: The filler comprises carbon black and modified nanocellulose in a mass ratio of 1:0.3-0.
5.
4. The port special tire tread rubber according to claim 3, characterized in that: The preparation method of the modified nanocellulose is as follows: Disperse nanocellulose in deionized water, add zinc acetate dihydrate, heat to 80-90°C, stir for 1-1.5h, adjust pH to 10-11 with sodium hydroxide solution, stir for 30-40min, filter, dry, and obtain an intermediate, wherein the mass ratio of nanocellulose to zinc acetate dihydrate is 1:0.15-0.25; The intermediate is dispersed in deionized water, hexadecyltrimethylammonium bromide is added, the temperature is raised to 60-70° C., the reaction is carried out for 2-3 hours, and the modified nanocellulose is obtained by centrifugation. The mass ratio of hexadecyltrimethylammonium bromide to the intermediate is 1:
1.
5. The port special tire tread rubber according to claim 3, characterized in that: The carbon black is pretreated as follows: Disperse carbon black in deionized water to form a dispersion with a concentration of 3-5wt%, add sodium thiosulfate, stir evenly to form a suspension, add a 30wt% hydrochloric acid solution, stir, wash with deionized water to a pH of 7, freeze-dry, and the mass ratio of carbon black to sodium thiosulfate and hydrochloric acid solution is 3.3:6-8:50-60.
6. The port special tire tread rubber according to claim 1, characterized in that: The antioxidant includes antioxidant RD and antioxidant 4020 in a mass ratio of 1.5:2.5-3.5; The softening oil is selected from at least one of aromatic oil, naphthenic oil and paraffin oil; The lubricant is selected from at least one of stearic acid, paraffin oil and silicone oil; The scorch retarder is selected from at least one of N-cyclohexylthiophthalimide and N,N-dibenzhydryl-1,6-hexanediisocyanate; The accelerator is selected from at least one of accelerator DM, accelerator NS and accelerator TMTD; The vulcanizing agent is selected from at least one of sulfur, benzoyl peroxide or sulfur monochloride; The anti-reversion agent is anti-reversion agent WK-901 or PK-900.
7. The process for preparing the tread rubber for port special tires according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing cigarette sheet rubber, neodymium-based butadiene rubber, modified aramid fiber, filler, softening oil, zinc oxide, lubricant, high temperature protective wax, antioxidant, dicyclopentadiene resin and anti-vulcanization reversion agent, and debonding at 155-165° C. to obtain a masterbatch; The master rubber is mixed with a vulcanizing agent, an accelerator and a scorch retarder, and kneaded, and discharged at 95-105° C. to obtain a tread rubber.